Anterior Chamber Angle Assessment by Anterior-segment Optical Coherence Tomography After Phacoemulsification With or Without Goniosynechialysis in Patients With Primary Angle Closure Glaucoma. Issue 9 (December 2015) - Shao, Tingting; Hong, Jiaxu; Xu, Jianjiang; Le, Qihua; Wang, Jiajian; Qian, Shaohong
Abstract : Purpose: To evaluate changes of anterior chamber angle (ACA) by anterior-segment optical coherence tomography (AS-OCT) in patients with primary angle closure glaucoma (PACG) following phacoemulsification (phaco) with or without goniosynechialysis (GSL). Methods: Patients with PACG recruited into 2 randomized controlled trials comparing phaco-GSL versus phaco were pooled for analysis. Images of ACA were obtained by AS-OCT before surgery, and at 1 and 2 weeks, and 1, 3, and 6 months after surgery. The following parameters were analyzed: angle opening distance (AOD) at 500 and 750 μm from the scleral spur, trabecular-iris space area (TISA) at 500 and 750 μm, angle recess area (ARA) at 500 and 750 μm, and scleral spur angle (SSA). Results: All parameters of ACA increased significantly after phaco-GSL ( P <0.001), whereas no increase occurred in the phaco group. Negatively significant correlations were found in ΔAOD500 ( P <0.05), ΔARA750 ( P <0.05), ΔTISA500 ( P <0.05), and ΔTISA750 ( P <0.05) at 1, 3, and 6 months, and ΔSSA ( P <0.05) at 3 and 6 months after phaco-GSL against Δ intraocular pressure (IOP). In the phaco-GSL group, 23 of 23 eyes had IOP<21 mm Hg without any antiglaucoma medication postoperatively. In the phaco group, 12 of 20 eyes (60%) had IOP<21 mm Hg without medication, 8 of 20 eyes required medication with IOP<21 mm Hg (15%) and uncontrollable IOP (25%) after surgery. Conclusions: On AS-OCT evaluation, ACA in eyes with PACG opened and widened significantly after phaco-GSL in our study. It is suggested that ΔAOD500, ΔARA750, ΔTISA500, ΔTISA750, and ΔSSA would provide valuable information to estimate the effectiveness of phaco-GSL. Abstract : Supplemental Digital Content is available in the text.